Thyroid Peroxidase Gene Mutation in Patients with Congenital Hypothyroidism in Isfahan, Iran. (29th May 2012) - Hashemipour, Mahin; Soheilipour, Fahimeh; Karimizare, Sakineh; Khanahmad, Hossein; Karimipour, Morteza; Aminzadeh, Sepideh; Kokabee, Leila; Amini, Massoud; Hovsepian, Silva; Hadian, Rezvaneh
Abstract : Background . Thyroid peroxidase gene (TPO) mutations are one of the most common causes of thyroid dyshormonogenesis in patients with congenital hypothyroidism (CH). In this study, the prevalence of TPO gene mutations in patients with thyroid dyshormonogenesis in Isfahan was investigated. Methods . In this cross-sectional study, genomic DNA of 41 patients with permanent CH due to thyroid dyshormonogenesis was extracted using the salting out method. The 17 exonic regions of the TPO gene were amplified. SSCP technique was performed for scanning of the exonic regions of the TPO gene, except exon 8. DNA sequencing was performed for those with different migration patterns in SSCP by chain termination method. Exon 8 was sequenced directly in all patients. In 4 patients, all fragments were also sequenced. Results . One missense mutationc .2669 G > A (NM_000547.5) at exon 15 (14th coding exon) in one patient in homozygous form and seven different single nucleotide polymorphisms (SNPs) in exons 1, 7, 8, 11, and 15 of TPO gene. Conclusion . The TPO gene mutations among CH patients with dyshormonogenesis in Isfahan were less frequent in comparison with other similar studies. It may be due to the presence of other unknown gene mutations which could not be detected by SSCP and sequencing methods.